(untitled) (AYUSHDHARA, 2024)
As per Ayurvedic principles, Shukra Dhatu is the vital reproductive tissue responsible for male fertility, often equated with semen. The nourishment and balance of Shukra Dhatu are essential for maintaining male reproductive health. Objective: To explore the impact of modern dietary habits and lifestyle practices on Shukra Dhatu and, consequently, on male infertility. Methods: The discussion integrates Ayurvedic concepts with modern dietary and lifestyle changes. The literature referencing from Charak Samhita, and through various modern text book, research journal and electronic database. Results: Modern processed diets deplete Shukra Dhatu, while nutrient-rich foods like dairy, nuts, and fruits enhance it. Improper food combinations disrupt digestion and accumulate toxins, harming Shukra Dhatu. Similarly, balanced exercise, sleep, and stress management support also Shukra Dhatu, whereas sedentary habits, irregular sleep, and toxins harm it. Conclusion: The shift towards modern dietary and lifestyle practices has contributed to increased oxidative stress, endocrine disruptions, and obesity, all of which are linked to male infertility. This article emphasizes the importance of balanced nutrition and a healthy lifestyle in promoting Shukra Dhatu health and preventing male infertility, thus helping to avoid such implications in future perspective.